Comparison of benefit between dabigatran and warfarin among patients with atrial fibrillation: A systematic review - Amal K Sulieman (Archives of Global Professionals, 2016)
Warfarin is recognized as the standard antithrombotic agent for stroke prevention. However, new oral anticoagulant such as dabigatran constitutes huge improvement to compensate for the limitation of warfarin. A literature review was performed to compare and contrast the overall benefit of dabigatran and warfarin among patients with atrial fibrillation. We utilized HighWire as the data source for randomized controlled trials based on inclusion and exclusion criteria (from January 2007 to September 2013). Descriptive and quantitative information related to stroke and major bleeding were extracted from each trial. After a comprehensive screening of 298 search results, 17 studies which enrolled a total of 127,594 patients were included. Warfarin was found to have higher mean event rates for incidence of stroke, major bleeding, and net clinical benefit compared to dabigatran 110 mg and dabigatran 150 mg. Dabigatran 110 mg has higher rate of stroke and net clinical benefit than dabigatran 150 mg with less major hemorrhage. Overall, dabigatran had higher efficacy and safety profile than warfarin. Further research is required to determine the clinical feasibility of dabigatran in real-life practice.